Pemberdayaan Lansia Melalui Pendekatan Spiritual, Kesehatan, dan Sosial dalam Program Sekolah Lansia Berdaya - Habibi, Ibnu; Susanto, M. Arif; Ihwanuddin, Ihwanuddin; Zanki, Aulia Singa (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service program aims to empower elderly women in Kapas Village, Kapas District and Pohbogo Village, Balen District, Bojonegoro Regency through the Sekolah Lansia Berdaya activity. This activity was attended by 52 elderly participants (26 people from each village) and carried the theme